Decoupling economic growth from carbon dioxide emissions in China's metal industrial sectors: A technological and efficiency perspective - Wang, Miao; Feng, Chao (The Science of the total environment, 2019)
As an energy-intensive industry, the mining, smelting, processing and production of metallic mineral resources consumes a large amount of fossil energy and simultaneously emits high amounts of carbon dioxide. This paper discusses the decoupling relationship between the economy and CO2 emissions of China's metal industry (MI) and then adopts an integrated decomposition approach (which reveals the roles of technology and efficiency) to investigate the drivers of CO2 emissions. The main findings indicate that, during 2000–2016: (1) China's MI experienced four decoupling stages (i.e., weak decoupling, expansive negative decoupling, expansive coupling, and strong decoupling) and was characterized by weak decoupling. Overall, China's MI showed a clear tendency toward strong decoupling. (2) Potential energy intensity change, investment efficiency decline, and production technological progress were three pivotal factors contributing to emission abatement. Industrial structure regulation and energy-saving technology advancement also made a small contribution to emission abatement and the decoupling state. (3) Investment scale expansion was the primary factor promoting emission growth and impeding the progress of decoupling. Meanwhile, the energy structure adjustment during the sampling period failed to inhibit emissions but restricted decoupling. Finally, possible policies for mitigating carbon emissions in China's MI are provided. The decoupling states of China's metal industry and their driving factors, including: energy structure adjustment (ΔCECS), industrial structure regulation (ΔCIS), investment efficiency change (ΔCIEF), investment scale expansion (ΔCI), potential energy intensity change (ΔCPEI), energy saving technology change (ΔCESTC), energy usage efficiency (ΔCEUEF), production technology change (ΔCPTC), and production efficiency (ΔCPEF). [Display omitted] •The decoupling state is studied from a technological and efficiency perspective.•A combined decomposition approach was applied for factors decomposition.•Investment scale expansion was the principal obstructor for decoupling progress.•Potential energy intensity change contributed to emission abatement and decoupling.•Investment efficiency decline and production technological progress facilitated decoupling.